Technological Addictions: Disease or Adaptive Behavior? - María Magdalena Caro Mantilla (Medisur)
In today's society, various affections are constantly appearing, and both the audiovisual media and part of the scientific community are coining new terms to name them. For some years, there has been a discussion of the so-called behavioral addictions and all are supposed to be familiar diseases such as addiction to work, shopping, exercise, etcetera. With the arrival of new technologies, the avalanche of diseases has increased even more. It has emerge the idea of addiction to video games, to mobile, to the internet and in recent years, to social networks, among others; however, to what extent they are true addictions, is a subject of deep debate, since they are not recognized as diseases in the current official classifications. The objective of this review is to contribute new elements to the technological addiction topic, according to the current mental health classification, about the new technologies impact on people’s behavior, and from the growing controversy perspective of considering them pathological or simply adaptive behaviors.